The Data-Creativity Nexus – Shaping the Future of Marketing in the Age of Artificial Intelligence - Alexander Hoffmann; Dominik K. Kanbach; Thomas Wykes-Sneyd (Marketing Review St.Gallen, 2023)
This study investigates the impact of artificial intelligence on marketing. Based on an extensive dataset of interviews with marketing executives, the study assesses current practices and argues that the future of marketing is inextricably linked to the effective integration of data and creativity. Thus, this research sheds light on this under-explored nexus.
Keywords: 650